Heart rate variability in children with congenital sensorineural deafness - Uçar, Tayfun; Tutar, Ercan; Tekin, Mustafa; Atalay, Semra (The Turkish Journal of Pediatrics, 2010)
We hypothesized that decreased sympathetic/parasympathetic balance as a result of the absence of auditory stimuli on the autonomic nervous system might be an explanation for our previous finding of lower mean heart rate in congenitally deaf children. To test our hypothesis, we obtained heart rate variability (HRV) data of 23 children with congenital sensorineural deafness from 24-hour Holter ECG recordings and compared them to data of 18 healthy children. HRV was measured by calculating time-domain and frequency-domain indexes from 24-hour recordings and from 6 hours of recordings obtained while subjects were sleeping. We additionally compared the HRV values obtained from children with and without GJB2 gene mutations. We did not find any significant difference in HRV parameters between deaf children and healthy children. There were also no significant differences in HRV parameters between deaf children with and without GJB2 mutations. We conclude that cardiac autonomic dysfunction does not seem to be present in patients with congenital sensorineural deafness.